Volume 3: Biomedical and Biotechnology Engineering 2014
DOI: 10.1115/imece2014-38648
|View full text |Cite
|
Sign up to set email alerts
|

Baseball Head Impacts to the Non-Helmeted and Helmeted Hydrid III ATD

Abstract: Traumatic brain injury may occur in baseball due to a head impact with a thrown, pitched, or batted ball. It has been shown that the average pitching speed of youth pitchers and high school pitchers is approximately 63 mph (28 m/s) and 74 mph (33 m/s), respectively. At pitching speeds of approximately 52 mph (23 m/s), the bat exit velocity (BEV) for metal bats has been shown to be approximately 100 mph (45 m/s). Head kinematics, such as linear and angular head accelerations, are often used to establish head in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Laboratory settings using anthropomorphic test dummies (ATD) are typically used to simulate potentially dangerous scenarios to evaluate the possible harm to a human, such as that used in car crash tests. Furthermore, similar setups have been used to quantify harm due to impacts in some sports and to evaluate protective gears, such as helmets [78,85,115]. One study used similar settings to assess the influence of taekwondo kicks and the peak velocity of the foot on the dynamics of the head [34].…”
Section: Related Impact Testsmentioning
confidence: 99%
“…Laboratory settings using anthropomorphic test dummies (ATD) are typically used to simulate potentially dangerous scenarios to evaluate the possible harm to a human, such as that used in car crash tests. Furthermore, similar setups have been used to quantify harm due to impacts in some sports and to evaluate protective gears, such as helmets [78,85,115]. One study used similar settings to assess the influence of taekwondo kicks and the peak velocity of the foot on the dynamics of the head [34].…”
Section: Related Impact Testsmentioning
confidence: 99%
“…Projectile impacts typically produce shorter contact durations, and in some circumstances have been reported to be lower than 2 ms. 7,24,25 Additionally, Raymond 26 observed skull deformation and excitation of the resonance frequency of the skull when impacting a human head with a cylindrical metal puck (diameter 38 mm, mass 103 g) at impact speeds (33.6 6 1.4 m/s) comparable to those seen in projectile sports. When assessing projectile impacts in a laboratory setting, Raymond 26 reported that the dynamic response of the Hybrid-III headform is unrealistic in impacts that produce areas of high-pressure, as the skull component is stiffer than human tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Dummies that report the head acceleration were also considered to evaluate the potential injuries to the head (e.g. in industrial robots and in sports [24,38,50]). Similarly, the impact setup in this study will use the peak linear head acceleration only as an indicator to sudy the influence of the considered factors.…”
Section: Head Severity Indexmentioning
confidence: 99%